2018
DOI: 10.5380/rcc.v10i1.48790
|View full text |Cite
|
Sign up to set email alerts
|

Propriedades da auditora contínua e auditoria de sistemas: uma análise bibliométrica e sociométrica na base scopus e no Congresso Internacional de Gestão da Tecnologia e Sistemas de Informação (Contecsi)

Abstract: O presente trabalho tem como objetivo analisar as características da produção científica sobre auditoria contínua e auditoria de sistemas apresentadas na base de dados internacional da scopus e no Contecsi nos anos de 2004 a 2014. Para tanto, realizou-se pesquisa descritiva, sendo que o problema foi abordado de forma quantitativa e como procedimento utilizou-se o delineamento documental. Foi utilizado as palavras-chaves auditoria, sistemas e contínua para a seleção dos artigos e a amostra final correspondeu a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The highest cited country was clearly the USA and followed by Hong Kong in citation per publication. The dominance of the USA and Australia was supported by Öztürk and Yilmaz (2018) and Folador et al (2018) mentioned the productivity of the USA. It was found that Holland, Canada, and the UK are leading in terms of citation per publication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The highest cited country was clearly the USA and followed by Hong Kong in citation per publication. The dominance of the USA and Australia was supported by Öztürk and Yilmaz (2018) and Folador et al (2018) mentioned the productivity of the USA. It was found that Holland, Canada, and the UK are leading in terms of citation per publication.…”
Section: Discussionmentioning
confidence: 99%
“…Melo Ribeiro (2015) used bibliometric and social network analysis methods to analyse 107 scientific studies on a journal published in Brazil for 1999-2013 period. Folador et al (2018) analysed a total of 96 articles between 2004-2014 on international Scopus and Contesci databased on continuous audit and system audit fields. Eulerich (2019b, 2019a) analysed a total of 170 publications between 1926 and 2016 on leading accounting journals on internal audit topic.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous Auditing (CA) is considered by many authors as the new paradigm of Internal Auditing (IA) (Kiesow et al, 2016), hence the need to understand its basic concepts, the main guidelines proposed by international organizations, the need, and the importance of this method for modern auditing. Especially in a scenario of organizational environment dominated by information and communication technologies (Folador et al, 2018). Regarding its definition, Kuhn, and Sutton (2010) and Rikhardsson and Dull (2016) define CA as a method of data analysis very close to real time, considering a set of predetermined rules.…”
Section: Continuous Auditingmentioning
confidence: 99%